Evaluation method using a transmission electron microscope
The use of a gas cluster ion beam to thin organic samples beyond conventional limits addresses the challenge of surface damage in TEM, enabling high-quality observations by minimizing scattering and enhancing data quality.
Patent Information
- Application Number
- JP2021177084
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-29
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-10-29
AI Technical Summary
Existing methods struggle to produce ultra-thin samples of organic materials for transmission electron microscopy (TEM) without introducing surface damage layers, which complicates high-resolution observations due to multiple scattering of electron beams.
Utilizing a gas cluster ion beam (GCIB) to further thin samples prepared by conventional methods like FIB or ion milling, effectively removing surface damage while maintaining the internal structure integrity.
Enables the production of ultra-thin organic samples with minimal surface damage, allowing for high-quality TEM/STEM observations and EELS measurements by reducing multiple scattering effects.
Smart Images

Figure 0007610498000001 
Figure 0007610498000002 
Figure 0007610498000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an evaluation method using a transmission electron microscope (hereinafter also referred to as TEM), and more particularly to a method of irradiating a gas cluster ion beam onto a TEM observation sample thinned by a conventional method, to prepare an even thinner TEM observation sample, and to perform TEM measurement. [Background technology]
[0002] By mixing multiple components, it is possible to create highly functional organic materials such as polymer materials. In order to improve functionality, it is necessary to precisely control the structure of the domains of each component on the nanometer order. Transmission electron microscopes are commonly used as a method for evaluating such fine structures. Among the observation methods using TEM, the technique of combining scanning transmission electron microscopy (STEM), which focuses an electron beam into a probe shape and scans the sample surface to create an image, with energy dispersive X-ray spectroscopy (EDX) and electron energy loss spectroscopy (EELS) to perform elemental analysis and chemical state analysis in localized areas is a very useful analytical technique. In particular, in recent years, the development of aberration correction devices for the lenses of TEM devices and high-sensitivity detectors has made it possible to observe with high spatial resolution and perform elemental analysis and chemical state analysis in microscopic areas.
[0003] For TEM measurements, the electron beam must pass through the sample, and a thin film sample with a thickness of several hundred nm or less must be prepared. Sample thinning techniques generally used include ion milling, focused ion beam (FIB), ultrathin sectioning, and electrolytic polishing. In particular, high-resolution TEM / STEM observations and EELS measurements are susceptible to the effects of multiple scattering, in which the incident electron beam is scattered multiple times in the sample before passing through it, which often makes data interpretation difficult. In order to obtain high-quality data in these measurements, it is desirable to prepare samples with a thickness of approximately 20 nm or less and suppress the effects of multiple scattering.
[0004] For hard materials such as semiconductor materials, metal materials, and ceramic materials, it is possible to prepare samples with a thickness of approximately 20 nm or less using conventional ion milling and FIB methods. On the other hand, organic materials are soft and tend to bend when thinned, so even if ion milling, FIB, or ultra-thin sectioning are used, the limit is that the thickness can be reduced to approximately 50 to 100 nm. Furthermore, thin film samples finished using ion milling and FIB methods have a damage layer of several to several tens of nm on the surface (the internal structure of the sample is altered), so it has been difficult to prepare ultra-thin samples with a thickness of 20 nm or less while maintaining the original structure of the sample.
[0005] A commonly used method for thinning a material while suppressing the generation of a damaged layer is to lower the beam acceleration voltage in the ion milling or FIB method. However, while this method is capable of removing only the surface damaged layer of hard materials, it is difficult to remove only the surface damaged layer of organic materials even if the acceleration voltage is lowered, and no successful examples have been reported.
[0006] As a method for thinning without introducing a surface damage layer of FIB processing, a method has been devised in which a thin film sample that has been previously subjected to electrolytic polishing is subjected to FIB processing while shielding the ion beam with a shielding plate (Patent Document 1). However, this method is intended for steel materials, and application to organic materials is not envisaged. In addition, a method has also been devised in which the surface damage layer of a sample thinned by ion milling is removed by chemical etching (Patent Document 2). However, this method is intended for semiconductor materials, and it is difficult to apply chemical etching to organic materials. In addition, as a method for thinning while removing the surface damage layer, a method has also been proposed in which low acceleration voltage ion milling is additionally performed after FIB processing (Patent Document 3). However, this method is also intended for hard materials, and it is difficult to effectively remove the damage layer from organic materials.
[0007] On the other hand, from the viewpoint of removing the surface damage layer of an organic material, a method using a gas cluster ion beam (hereinafter, GCIB) has been proposed (Non-Patent Document 1). GCIB is an ion beam consisting of giant particles in which hundreds to thousands of gas atoms are bonded, and it is possible to scrape the surface of a sample by colliding it with a solid surface at high speed. Since the energy per atom is small at a few eV, GCIB can scrape only the surface of an organic material without destroying its internal structure, and it is used to remove the contaminated layer or damaged layer on the top surface of a sample before performing surface analysis by time-of-flight secondary ion mass spectrometry (hereinafter, TOF-SIMS) or X-ray photoelectron spectroscopy (hereinafter, XPS). However, the application of GCIB reported so far has been to the surface of a bulk sample, which is a TOF-SIMS or XPS measurement sample, and no examples have been reported for TEM thin film samples. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2013-205017 A [Patent Document 2] Japanese Patent Application Publication No. 05-018873 [Patent Document 3] JP 2004-199969 A [Non-patent literature]
[0009] [Non-Patent Document 1] S. Iida, Cross-section Observation of Inorganic / Organic Materials by Using FIB-TOF-SIMS. Journal of Surface Analysis 2016, 23, 11 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in consideration of the current situation as described above, and provides a method for further thinning a sample that has been thinned by ultrathin sectioning, FIB, or ion milling while suppressing the generation of a damaged layer. [Means for solving the problem]
[0011] In order to achieve the above object, the present invention is as follows.
[0012] This is an evaluation method using a transmission electron microscope in which a thin film sample is further thinned using the gas cluster ion beam method and then measured. Effect of the Invention
[0013] The present invention makes it possible to prepare ultra-thin slice samples of organic materials that minimize the generation of surface damage layers, which was difficult to achieve with conventional techniques, in transmission electron microscope evaluation, and by using these slice samples, the effects of multiple scattering of incident electron beams in the sample can be suppressed. In particular, it becomes possible to obtain high-quality data in high-resolution TEM / STEM observation and EELS measurement. The present invention is not limited to high-resolution TEM / STEM observation and EELS measurement, and it is possible to provide high-quality data for various measurement methods performed with TEM equipment. [Brief description of the drawings]
[0014] [Figure 1] 1 is a flow chart showing a procedure for thinning a film according to the present invention. [Diagram 2] Electron beam tomography was performed on a polyethylene sample that was thinned to a thickness of approximately 140 nm using the FIB method and then electron-stained with RuO4. The obtained 3D data was observed from the cross-sectional direction of the sample. [Diagram 3] Polyethylene was thinned to a thickness of approximately 140 nm using the FIB method, and then further thinned to approximately 70 nm using GCIB. The sample was then electron-stained with RuO4, and electron tomography measurements were performed. The resulting 3D data was observed from the cross-sectional direction of the sample. [Figure 4]This is the result of STEM observation of a polyethylene sample that was thinned to a thickness of approximately 140 nm using the FIB method and then stained with RuO4 electrons. [Diagram 5] This is the result of STEM observation of a polyethylene sample that was thinned to a thickness of approximately 140 nm using the FIB method, then further thinned to approximately 70 nm using GCIB and stained with RuO4 electrons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] Examples of organic materials that are the subject of the present invention include polyolefins such as polyethylene and polypropylene, crystalline polymer materials such as polyamide, polyacetal, saturated polyester, polyvinylidene fluoride, and polyphenylene sulfide, amorphous polymer materials such as polystyrene, high impact polystyrene, acrylonitrile butadiene styrene copolymer resin, polyvinyl chloride, polycarbonate, polyphenylene ether, and polysulfone, and thermosetting resins such as phenol resin, melamine resin, unsaturated polyester resin, and epoxy resin. However, organic materials to which the present invention can be applied also include organic materials other than those mentioned above. In the evaluation method using a transmission electron microscope of the present invention, a sample containing an organic material, such as a sample composed of only a single or multiple organic materials or a mixed sample of an organic material and an inorganic material, is preferably thinned by a conventional TEM observation sample preparation method such as an ultrathin section method, an FIB method, or an ion milling method. In the present invention, thinning refers to a thickness that allows an electron beam accelerated to 200 kV to pass through the sample, and means processing the sample into a thickness of about 5 nm to 500 nm.
[0017] A preferred example is to fix the thin film sample, while it is still fixed on the TEM observation mesh, together with the TEM observation mesh on a glass substrate or the like, and introduce the resultant sample into a GCIB device.
[0018] A preferred example is to finish a thin film sample even thinner without altering the internal structure while removing the surface damage layer by GCIB. In some cases, a preferred example is to irradiate the back side with GCIB to remove the damage layer on the back side as well.
[0019] It is preferable to remove the ultrathin sample together with the TEM observation mesh from the glass substrate, etc., mount it on a TEM sample holder, and introduce it into a TEM device. Regarding TEM measurement, it is preferable to use an electron beam with as low a current density as possible and perform the measurement in a short time in order to suppress damage caused by electron beam irradiation.
[0020] The present invention preferably comprises three steps: a pre-thinning step using a conventional thinning method, a thinning finish step (ie, further thinning) using GCIB, and a thin film measurement step using TEM.
[0021] <1. Pre-thinning process> The thinning pre-process can be carried out by several types of pre-treatment. Specifically, three types of techniques are preferably exemplified: ultra-thin sectioning, FIB, and ion milling. Below, an example of a preferred pre-treatment method by each technique will be described in more detail.
[0022] <1-1.Ultrathin section method> A block sample of organic material is cut to an appropriate size in advance, and then ultrathin sections are made with an ultramicrotome device, with a thickness setting of tens to hundreds of nm. If the size of the organic material to be measured is small, it is desirable to embed it in resin or the like beforehand. If it is difficult to process at room temperature, it is desirable to cut it under cryo-conditions. The cut ultrathin sections are suspended on a TEM observation mesh with a diameter of 3 mm. The material of the TEM observation mesh and the presence or absence of a supporting film such as a carbon film are not important.
[0023] <1-2.FIB method> A block sample of organic material cut to an appropriate size is introduced into the FIB device. For example, a gallium ion beam is used to remove the periphery of the sample surface to produce small pieces measuring several μm in length, 20 μm in width, and 10 μm in depth. A tungsten needle is grounded on the small pieces, and the small pieces and the needle are bonded together by carbon deposition. The needle to which the small pieces are attached is moved, and the small pieces are fixed to the side of a crescent-shaped TEM observation mesh with a diameter of 3 mm by carbon deposition, after which the needle and the small pieces are cut off using a gallium ion beam. The small pieces are irradiated with a gallium ion beam parallel to the depth direction, and polished with the ion beam until the thickness of several μm in length is reduced to tens to hundreds of nm. If processing is difficult at room temperature, it is preferable to cut under cryo-conditions.
[0024] <1-3. Ion milling method> A block sample of organic material, cut in advance to a size of, for example, 2 mm in length, 2 mm in width, and 1 mm in height, is attached to a single-hole mesh with a diameter of 3 mm. Using a dimple grinder or similar, the organic material block sample is mechanically polished to a thickness of several tens of μm so that it has a cone shape. The sample is then placed in an ion milling device and irradiated with an argon ion beam until a hole is made in the center of the organic material block sample. If processing is difficult at room temperature, it is preferable to cut under cryo-conditions.
[0025] <2. Thinning process (further thinning)> The sample prepared in the pre-thinning process is attached to a glass substrate or the like together with the TEM observation mesh using carbon tape or the like. The glass substrate with the sample attached is introduced into a GCIB device. The position of the sample supported on the TEM observation mesh is confirmed using a camera attached to the GCIB device, and the GCIB is irradiated to the desired position. Since the etching speed by GCIB differs for each material, it is desirable to determine the amount of GCIB current and irradiation time in advance using a test sample. If damage layers have occurred on both the front and back sides of the sample in the pre-thinning process, it is desirable to irradiate one side with GCIB, turn over the TEM observation mesh, attach it to the glass substrate again, and irradiate the other side with GCIB. In this process, a thin film with a sample thickness of 20 nm or less is prepared.
[0026] <3. Thin film measurement process> The sample prepared in the thin film finishing process is removed from the glass substrate together with the TEM observation mesh and attached to a TEM holder. The TEM holder is introduced into the TEM body, and the sample is irradiated with an electron beam to perform measurements. Since polymeric materials that have not been subjected to electronic staining are vulnerable to electron beam irradiation, it is desirable to use an electron beam with as low a current density as possible and to perform measurements in a short time. If possible, it is desirable to use a high-sensitivity camera or detector, or to perform measurements under cryo-conditions.
[0027] Although the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the gist of the present invention.
[0028] For example, in the present invention, the pre-thinning process is an example of a conventional method for preparing a thin film sample for TEM observation, but it is also possible to prepare a thin film sample for TEM observation having a thickness of tens to hundreds of nm through other known techniques, other known implementation steps, or other known implementation conditions.
[0029] In the evaluation using a transmission electron microscope of the present invention, it is preferable to set the electron beam irradiation current value to 10 pA or less, which makes it possible to perform the measurement while suppressing the effects of destruction of the phase separation structure, the crystalline / amorphous structure, or changes in the chemical bond state caused by the electron beam irradiation of the sample.
[0030] In the evaluation by the transmission electron microscope of the present invention, it is preferable to use a high-sensitivity detector such as a direct detection detector or a complementary metal-oxide semiconductor (hereinafter, CMOS) detector, which can suppress the influence of the phase separation structure, destruction of the crystal / amorphous structure, or change in the chemical bond state caused by the irradiation of the sample with an electron beam.
[0031] In the evaluation using a transmission electron microscope of the present invention, it is preferable to set the electron beam irradiation current value to 10 pA or less and use the above-mentioned high-sensitivity detector, which allows the measurement to be performed while particularly suppressing the effects of destruction of the phase separation structure, crystalline / amorphous structure, or changes in the chemical bond state caused by electron beam irradiation of the sample. EXAMPLES
[0032] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the scope of the examples.
[0033] Example 1 [Additional thinning by GCIB and TEM tomography measurement of polyethylene thin film samples prepared by FIB method] A pre-thinning process was carried out using the FIB method to prepare a polyethylene film sample with a thickness of 140 nm. The sample thickness was confirmed using an SEM attached to the FIB device. The sample was fixed to a half-moon shaped Mo mesh for TEM observation. The mesh was attached to a glass substrate using carbon tape and introduced into the GCIB device. The sample position was confirmed using a camera inside the device, and the GCIB was irradiated on one side only for 70 seconds. The GCIB conditions used were an acceleration voltage of 5 keV and a beam current of 4 nA.
[0034] The thickness of the GCIB-irradiated sample was measured by TEM tomography. A high-tilt TEM holder was used to obtain 131 TEM images at 1° intervals from -65° to +65°. The measurement magnification was 50,000x. To minimize the electron beam dose, a high-sensitivity CMOS camera was used to obtain the TEM images. The obtained continuous tilt TEM images were reconstructed in 3D using the filtered back projection (FBP) method. Figure 3 shows the obtained 3D data observed from a direction perpendicular to the sample thickness direction. The sample thickness was measured to be 70 nm, confirming a 70 nm reduction from before GCIB irradiation. In fact, the sample could be further thinned with an etching rate of 1 nm / 1 s, and it is possible to thin the sample to less than 20 nm by adjusting the irradiation time.
[0035] Example 2 [Additional thinning of polyethylene thin film samples prepared by FIB method using GCIB and observation of the internal structure using dye-transfer TEM] A pre-thinning process was carried out using the FIB method to prepare a polyethylene film sample with a thickness of 140 nm. The sample thickness was confirmed using an SEM attached to the FIB device. The sample was fixed to a half-moon shaped Mo mesh for TEM observation. The mesh was attached to a glass substrate using carbon tape and introduced into the GCIB device. The sample position was confirmed using a camera inside the device, and the GCIB was irradiated on one side only for 70 seconds. The GCIB conditions used were an acceleration voltage of 5 keV and a beam current of 4 nA.
[0036] The obtained thin film samples were subjected to RuO4 electronic staining, and the lamellar structure, which indicates the crystalline / amorphous regions inside the polyethylene, was observed. The lamellar structure was not observed in the sample not irradiated with GCIB, but was clearly observed in the sample irradiated with GCIB. In other words, the presence of surface damage in the sample not irradiated with GCIB prevents the dye from penetrating into the interior, whereas the surface damage layer in the sample irradiated with GCIB has been removed, allowing the dye to penetrate to the interior, making it possible to observe the lamellar structure inside the sample.
Claims
1. This is an evaluation method using a transmission electron microscope in which a thin film sample is further thinned using a gas cluster ion beam method, and the surface irradiated with the gas cluster ion beam is then irradiated with an electron beam for measurement.
2. 2. The evaluation method using a transmission electron microscope according to claim 1, wherein the sample is a sample made of only one or more organic materials, or a mixed sample of an organic material and an inorganic material.
3. 3. The method for evaluation using a transmission electron microscope according to claim 1 or 2, in which a sample that has been thinned by a method selected from the group consisting of a focused ion beam method, an ultrathin section method, and an ion milling method is irradiated with a gas cluster ion beam on one or both sides to further reduce the thickness and then measured.
4. 4. The evaluation method using a transmission electron microscope according to claim 1, wherein a layer of altered chemical structure on the surface of the thinned sample is removed by a gas cluster ion beam.
5. 5. The method for evaluation using a transmission electron microscope according to claim 1, wherein the sample is thinned by irradiating it with a gas cluster ion beam without altering the phase separation structure, crystalline / amorphous structure, or chemical bonding state inside the sample.
6. 6. The method for evaluation using a transmission electron microscope according to any one of claims 1 to 5, wherein, in the evaluation using a transmission electron microscope, the current value of the electron beam irradiation is set to 10 pA or less, or a high-sensitivity detector is used, or both are used, thereby suppressing the effects of destruction of a phase separation structure or a crystalline / amorphous structure, or a change in a chemical bonding state caused by irradiation of an electron beam on a sample, and performing the measurement.
Citation Information
Patent Citations
Sample preparation for transmission electron microscope
JP1993018873A
Sample holder for charged particle beam device
JP2004199969A
Apparatus and method for preparing minute thin film sample for transmission electron microscope
JP2013205017A
Neutral beam processing method based on gas cluster ion beam technology and products manufactured by it
JP2018514939A